2017
DOI: 10.1364/oe.25.013199
|View full text |Cite
|
Sign up to set email alerts
|

Integrated perovskite lasers on a silicon nitride waveguide platform by cost-effective high throughput fabrication

Abstract: Metal-halide perovskites are a class of solution processed materials with remarkable optoelectronic properties such as high photoluminescence quantum yields and long carrier lifetimes, which makes them promising for a wide range of efficient photonic devices. In this work, we demonstrate the first successful integration of a perovskite laser onto a silicon nitride photonic chip. High throughput, low cost optical lithography is used, followed by indirect structuring of the perovskite waveguide. We embed methyla… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
61
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(61 citation statements)
references
References 32 publications
0
61
0
Order By: Relevance
“…Most of the following work on perovskite thin films concentrated on the workhorse composition for solar cells, methylammonium (CH 3 NH 3 /MA) lead (Pb) triiodide (I 3 ) that emits around 790 nm. Random lasers [18], whispering gallery mode lasers [19][20][21][22], distributed feedback lasers [23][24][25], vertical cavity lasers [26,27] and photonic crystals lasers have been demonstrated using this CH 3 NH 3 PbI 3 composition [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Most of the following work on perovskite thin films concentrated on the workhorse composition for solar cells, methylammonium (CH 3 NH 3 /MA) lead (Pb) triiodide (I 3 ) that emits around 790 nm. Random lasers [18], whispering gallery mode lasers [19][20][21][22], distributed feedback lasers [23][24][25], vertical cavity lasers [26,27] and photonic crystals lasers have been demonstrated using this CH 3 NH 3 PbI 3 composition [28,29].…”
Section: Introductionmentioning
confidence: 99%
“…Due to their promising electronic and optical properties, tremendous progress has been made in the performance of perovskites solar cells. [6,7] Such films have been incorporated into a variety of optical cavities, including whispering gallery mode cavities, [5,[8][9][10] vertical cavities, [4,11] distributed feedback (DFB) cavities, [12][13][14][15][16] and photonic crystal cavities. [3][4][5] Simple, solution-based fabrication of perovskites allows the fabrication of thin films, which exhibits optical gain within a wide spectral range.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, inductively coupled plasma chemical vapor deposition (ICP-CVD) technique has been developed to deposit SiN x film under ultra-low temperature [25][26][27]. In our previous work, we have reported that a high quality SiN x film with thickness up to 2 μm can be achieved in a single growth process under ultra-low temperature circumstance [27], which shows great potential for active passive hybrid photonic integration [28,29].…”
Section: Introductionmentioning
confidence: 99%